ADHD in Children: Comprehensive Review of Symptom Manifestations, Predisposing Factors, Early Detection, Diagnosis, and Clinical Interventions - Elizar, Lale Justin Amelinda; Muharis, Nihal Ahmad (Jurnal Biologi Tropis, 2025)
Attention Deficit/Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder in children, characterized by symptoms of inattention, hyperactivity, and impulsivity that are inappropriate for developmental level. This disorder has a significant impact on children's academic, social, and emotional development. This article presents a literature review of risk factors, diagnosis, and management of ADHD in children based on published scientific sources spanning 5 to 10 years. The method used is a systematic literature review of national and international journals. The results of the study indicate that ADHD has a multifactorial etiology and requires an integrated approach to treatment, combining pharmacological and nonpharmacological interventions. A comprehensive understanding of ADHD is essential to support effective early intervention.